Assessing the Suitability of Snail-Shell Powder as a Partial Replacement of Cement in Concrete Production. - Mukundane, Ivan (Kabale University, 2024)
Concrete is a mixture of aggregates and binders and among the concrete ingredients, the binder which is usually cement is a costly and environmentally unfriendly element, especially during its manufacture, and has led to resource depletion. Concrete is considered the backbone of any construction work both economically and mechanically. It is a composite material resulting from a mixture of cement, water, and aggregates (both fine and coarse). It makes any shape when cast in any formwork and forms a solid mass when cured at a suitable temperature and humidity This research titled “Assessing the suitability of snail-shell powder as partial replacement of cement in concrete” aims at the utilization of snail shells as a partial replacement of ordinary Portland cement. Snail shells obtained from the lake shores of Albert in Uganda were washed and cleaned thoroughly with clean water. The shells were ground by a hammer mill into fine pieces in size. They were oven-dried under conditions of 150oc for 2 hours and sieved through the 0.075mm sieve to obtain the required powder. Their pozzolanic composition was done and found to contain elements such as Calcium-Oxide 85.413%m/m, Iron (iii) oxide 0.406%m/m, Silicon dioxide 8.561%m/m, Potassium oxide 0.212%m/m, Aluminum oxide as 4.250%m/m, Manganese(ii) oxide 0.308%m/m, Phosphorous pent oxide 0.002%m/m, Titanium oxide 0.015%m/m. Physical properties of snail shells, fine aggregates, and coarse aggregates were also done and found to be fineness modulus of sand 2.56, water absorption of sand 2.3%, specific gravity of sand 1.23, natural moisture content of sand 1.47%, water absorption and specific gravity of coarse aggregates as 0.5% and 2.68 respectively, bulk density of coarse aggregates of 1555.56kg/m3 specific gravity and water absorption of the snail-shell sample as 2.95 and 2.02% respectively and fineness of SSP as 92.8%. Blended pastes containing OPC and SSP at different percentage replacements, 0%, 5%, 7.5%, 10%, and 12.5% were investigated for workability, and compressive strength of grade 20 Concrete at different days ie 7. 14 and 28 days It was found that 10% replacement of SSP gave the maximum concrete and the desired strength of 19.1MPa at 28 days while an increase in the % replacement lowered the workability of concrete.